Затримки транспортного потоку в межах зупинних пунктів міського громадського транспорту на двосмугових вулицях з двостороннім рухом - Ройко, Юрій; Максимюк, Сергій (Видавництво Львівської політехніки, 2018)
Assessment of delays in traffic flow movement within stopping points of urban public transport on two-line streets gives an opportunity to reveal and differentiate factors which cause their appearance and also to define general time losses on movement by such categories of roadways for individual and public transport.
Traffic flow delays within stopping points of urban public transport on two-line streets with two-way traffic
Keywords: 656.11